2004
DOI: 10.1161/01.cir.0000144310.04433.be
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal–Pro-Brain Natriuretic Peptide Predicts Outcome After Hospital Discharge in Heart Failure Patients

Abstract: Background-Heart failure (HF) is responsible for a huge burden in hospital care. Our goal was to evaluate the value of N-terminal-pro-brain natriuretic peptide (NT-proBNP) in predicting death or hospital readmission after discharge of HF patients. Methods and Results-We included 182 patients consecutively admitted to hospital because of decompensated HF.Patients were followed up for 6 months. The primary end point was death or readmission. Twenty-six patients died in hospital. The median admission NT-proBNP le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
359
3
21

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 650 publications
(417 citation statements)
references
References 33 publications
34
359
3
21
Order By: Relevance
“…In studies of people with CHF, a decrease in BNP >30% during hospitalization predicted a 45% decrease in mortality risk or >40% survival advantage 24. In addition, another study in people with CHF showed that a >30% decrease in NT‐proBNP concentrations was associated with fewer adverse events, such as readmission for CHF or death within 6 months 29. In the current study, whereas BNP was not measured, achieving >30% decrease in NT‐proBNP concentrations was not associated with survival time in cats, although this may be related to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of people with CHF, a decrease in BNP >30% during hospitalization predicted a 45% decrease in mortality risk or >40% survival advantage 24. In addition, another study in people with CHF showed that a >30% decrease in NT‐proBNP concentrations was associated with fewer adverse events, such as readmission for CHF or death within 6 months 29. In the current study, whereas BNP was not measured, achieving >30% decrease in NT‐proBNP concentrations was not associated with survival time in cats, although this may be related to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the plasma concentration of BNP is emphasized as a parameter of the severity of heart failure, a prognostic factor, and an item for evaluating the treatment response [15,16,18]. In addition, some studies have indicated that NT-proBNP is diagnostically more significant than BNP [3,5,6,10,11].…”
mentioning
confidence: 99%
“…To our knowledge, this is the first investigation to assess the effect modification of BMI on the prognostic utility of NT‐proBNP levels on clinical outcomes in an acute HF population. Baseline and change in NT‐proBNP levels have been shown to be powerful prognostic factors in acute HF 32, 33, 34. With the prevalence of obesity rising in North America, as evidenced by 50% of patients in our study population categorized as obese and 16% severely obese, our analysis provides evidence that NT‐proBNP testing during acute HF exacerbation remains useful in patients with the highest or lowest BMIs.…”
Section: Discussionmentioning
confidence: 63%